Cluster initiative management: A potential for African women entrepreneurs in the informal sector. (August 2019) - Okeke-Uzodike, Obianuju E; Subban, Mogie
The paper examines the role cluster initiative management can play for women entrepreneurs in small medium enterprises in the South African informal sector economy as forms of employment. It looks inter-relationally into aspects that heighten awareness and significance of entrepreneurial development of women. The concept of cluster initiative management at local, national, regional and global levels in relation to rural women in the informal economy is of note. The paper contextualizes the cluster notion as an important approach especially for small and medium-sized enterprises to survive and compete successfully in changing business environments while identifying key issues for due consideration. The notion of clustering has evolved over time and four domains of women's economic empowerment are put forward. Methodology in the paper follows an exploratory study premised on reviewing existing literature through dimensions of cluster initiative management and its relevance in women entrepreneurial development. Findings of the study provide insights and recommendations into the provision of a favourable environment for cluster initiatives to flourish and draws attention of key policy-makers in decision-making that supports sustainability of women entrepreneurs towards self-employment in informal sectors of the economy.